Features of interdisciplinarity of modern pedagogy - Романюк, Світлана (My University, 2022)
The most important task of modern education is the formation of a highly developed personalitycapable of effectively assimilating knowledge, making non-standard decisions and thinking creatively. Modernization of the content of education, renewal of teaching methods and means are the basis of new pedagogical searches. The study of the problem of interdisciplinarity is important for the development of scientific, theoretical foundations of pedagogy, as well as for the practical activities of teachers. Interdisciplinarity will be able to provide a unified methodological basis for the subject system as a whole by highlighting systematizing scientific ideas that facilitate learning in all subjects. Interdisciplinary approaches are in line with the pressing problems of modern education. Since academic subjects are built in the logic of specific sciences, and all of them to one degree or another are related to each other, it becomes necessary to establish interdisciplinarity.Thus, the main purpose of the article is to determine the basic features of the interdisciplinarity of modern pedagogy. The research was carried out using the following theoretical methods: systems analysis and synthesis, induction and deduction, comparison, classification, generalization and systematization, idealization and abstraction.
Keywords: Interdisciplinarity; Modern pedagogy; Specialists; Student’s personality